THE ANALYSIS OF SENIOR HIGH SCHOOL STUDENTS’ MATHEMATICAL LITERACY VIEWED FROM PISA PROBLEMS - Rahmadhani, Elfi; Noviani, Julia; Putri, Hasni (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
Literacy skills are important in learning mathematics. Mathematical literacy skills are able to provide opportunities for students to understand the benefits and practicalities of mathematics in real life, solve real-life problems using mathematics and can also be applied in decision making. This study aims to describe students' mathematical literacy abilities in terms of PISA problems. This research is descriptive qualitative. Selection of research subjects using purposive sampling. The research subjects in this study were students of Al Azhar Takengon Integrated High School, class XII Science, consisting of two students with high abilities. The data collection technique used the PISA problems and interviews. Data were analyzed using data analysis techniques proposed by Miles and Huberman. This study uses time triangulation to check the validity of the data. The research results showed that the profile of the mathematical literacy ability of students with high mathematical ability in solving PISA problems is classified as good. Subjects are able to think at an advanced level and students are able to complete the six levels of PISA problems given by fulfilling each mathematical process in mathematical literacy; formulate, employ, and interpret.   Kemampuan literasi menjadi hal yang penting dalam pembelajaran matematika. Kemampuan literasi matematika mampu memberikan kesempatan pada siswa untuk memahami manfaat dan kepraktisan matematika dalam kehidupan nyata, memecahkan masalah pada kehidupan nyata dengan menggunakan matematika serta dapat juga diaplikasikan dalam pengambilan keputusan. Penelitian ini bertujuan untuk mendeskripsikan kemampuan literasi matematika siswa ditinjau dari soal PISA. Penelitian ini merupakan penelitian kualitatif deskriptif. Pemilihan subjek penelitian menggunakan purposive sampling. Subjek penelitian pada penelitian ini adalah siswa SMA Terpadu Al Azhar Takengon kelas XII IPA yang terdiri dari dua orang siswa yang berkemampuan tinggi. Pengumpulan data menggunakan tes PISA dan wawancara. Data dianalisis dengan menggunakan teknik analisis data yang dikemukakan oleh Miles dan Huberman. Penelitian ini menggunakan triangulasi waktu untuk pemeriksaan keabsahan data. Hasil penelitian menunjukkan bahwa profil kemampuan literasi matematis siswa berkemampuan matematika tinggi dalam menyelesaikan soal PISA tergolong baik. Subjek sudah mampu berpikir pada tingkat lanjut dan mampu menyelesaikan enam level soal PISA yang diberikan dengan memenuhi setiap proses matematika pada literasi matematis, yaitu memformulasi, menerapkan, dan menginterpretasikan